On the compressive strength prediction for concrete masonry prisms - Barbosa, C. S. (2010)
The results of a combined experimental program and numerical modeling program to evaluate the behavior of ungrouted hollow concrete blocks prisms under uniaxial compression are addressed. In the numerical program, three distinct approaches have been considered using a continuum model with a smeared approach, namely plane-stress, plane-strain and three-dimensional conditions. The response of the numerical simulations is compared with experimental data of masonry prisms using concrete blocks specifically designed for this purpose. The elastic and inelastic parameters were acquired from laboratory tests on concrete and mortar samples that constitute the blocks and the bed joint of the prisms. The results from the numerical simulations are discussed with respect to the ability to reproduce the global response of the experimental tests, and with respect to the failure behavior obtained. Good agreement between experimental and numerical results was found for the peak load and for the failure mode using the three-dimensional model, on four different sets of block/mortar types. Less good agreement was found for plain stress and plain strain models.